An Augmented Reality System for Malaysian STPM Students Studying Chemistry - Ameen Faisal Salar, Mohammed; Kumar Appadurai, Naresh (International Journal of Psychosocial Rehabilitation, 2019)
Chemistry based laboratory experiments for upper high school level also known as Sijil Tinggi Persekolahan Malaysia (STPM) chemistry education has been a staple subject for the past 27 years as outlined by the Malaysian Higher Education Ministry. Even though safety standards and utilities have progressed throughout the years, the fundamental issue of student safety remains ever-present and remains the only major avenue of learning these experiments. Even though technological advancements have taken place, the lab experiments have been unchanged. The aim of this research is to justify the necessity of an alternate safer and practical avenue for learning chemical lab experiments using an Augmented Reality System. The paper discusses methods to create an Augmented Reality system for chemistry laboratory education that not only allows the students to learn experiments safely outside the boundaries of the chemistry lab but also teaches laboratory safety and tests their abilities. The research encompasses case studies and other research to support the above stated